Incorporating curriculum mapping as a method to increase approval plan precision. Issue 2 (7th February 2022) - Ramirez, Diana; Tabacaru, Simona
Abstract: This study incorporates curriculum mapping as a method to assess the effectiveness of approval plans supporting undergraduate psychology courses offered at a large research university. Usage data is aggregated over a nine-year period for 2, 917 monographs acquired between 2011 and 2017. Results show that curriculum mapping is effective for examining usage at a more granular level than using broad Library of Congress classification breakdowns. Analysis by content level and publisher provided insights into unused or low-usage monographs allowing for more precise profile adjustments. Though psychology profile adjustment decisions are discussed, this study can serve as a model for other subject areas.